Controlling the order of triblock copolymer via confinement induced by forced self-assembly. (March 2016) - Roland, Sébastien; Miquelard-Garnier, Guillaume; Gervais, Matthieu; Guinault, Alain; Sollogoub, Cyrille
Graphical abstract: Abstract: We report the making of multilayered self-assembled films by coextrusion, composed of alternated layers of confining polycarbonate and confined poly(styrene- b -butadiene- b -methyl methacrylate), whose blocks are chemically different from the confining polymer, and presenting a self-assembled morphology directly after extrusion. The triblock copolymer layers thicknesses was varied from few hundreds to few tens of nanometers. As the triblock layer thickness is decreased and the draw ratio is increased, the triblock morphology is constrained into a preferential orientation and higher long-range order is observed by transmission electron microscopy and small angle X-ray scattering. This one-step and industrially scalable method allowing long-range ordering of the nanodomains is of interest for many engineering applications for which producing large quantity of materials is necessary.